2009
DOI: 10.1093/chemse/bjp008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma Membrane Calcium ATPases in Calcium Clearance from Olfactory Sensory Neurons

Abstract: Odorants cause Ca(2+) to rise in olfactory sensory neurons (OSNs) first within the ciliary compartment, then in the dendritic knob, and finally in the cell body. Ca(2+) not only excites but also produces negative feedback on the transduction pathway. To relieve this Ca(2+)-dependent adaptation, Ca(2+) must be cleared from the cilia and dendritic knob by mechanisms that are not well understood. This work focuses on the roles of plasma membrane calcium pumps (PMCAs) through the use of inhibitors and mice missing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Additionally, all isoforms of plasma membrane calciumtransporting ATPase have been detected in our proteomic study. These calcium pumps are present in OSN [50] and participate in the clearance of accumulated calcium within the olfactory cilia during the odor response [51,52]. In accordance with HBPP studies, [45] a high number of GTPases have been also identified in OB such as 19 Rab GTPases, 6 Arf GTPases, and 5 dynamins.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, all isoforms of plasma membrane calciumtransporting ATPase have been detected in our proteomic study. These calcium pumps are present in OSN [50] and participate in the clearance of accumulated calcium within the olfactory cilia during the odor response [51,52]. In accordance with HBPP studies, [45] a high number of GTPases have been also identified in OB such as 19 Rab GTPases, 6 Arf GTPases, and 5 dynamins.…”
Section: Discussionsupporting
confidence: 54%
“…After transfected with interfering RNA to suppress the expression of PMCA2, primary neurons have higher basal Ca 2+ level, slower Ca 2+ recovery after stimulation, and partial return to pre-stimulation Ca 2+ level [20]. Similarly, the olfactory sensory neurons (OSNs) from PMCA2 knockout mice are unable to reverse Ca 2+ to pre-stimulated level after stimulation [21]. It is well known that Ca 2+ overload in chondriosome is the main reason for the death of neural cells.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
“…This Cl − efflux through the Ca 2+ -activated Cl channel gives rise to an inward current that adds to (i.e., amplifies) the inward CNG current, leading to olfactory signal amplification. The odorant-induced elevation in intracellular Ca 2+ concentration is subsequently nullified by a 4Na + /Ca 2+ , K + exchanger (28)(29)(30) and controvertibly also a Ca 2+ -ATPase (31)(32)(33)(34)(35). Despite the supposedly established facts about olfactory transduction described above, this picture has relapsed into confusion in recent years with respect to both adaptation and signal amplification (3).…”
mentioning
confidence: 99%